Isolation and Characterization of a Novel Diethylstilbestrol-Degrading Bacillus subtilis JF and Biochemical Degradation Metabolite Analysis - Deng, Weiqin; Zhao, Yun; Hu, Kaidi; Chen, Shujuan; He, Li; Ao, Xiaolin; Zou, Likou; Hu, Xinjie; Yang, Yong; Liu, Shuliang (Frontiers in Microbiology, 2019)
Diethylstilbestrol (DES) can adversely affect the immune system of developing foetuses or even elicit toxic responses such as nerve toxicity and genotoxicity in human beings, thereby warranting methods to remove DES from the environments. The present study characterised a novel DES-degrading Bacillus subtilis JF and analysed the degradation metabolites. The strain was collected at the China General Microbiological Culture Collection Center (Collection number: CGMCC 7950). The environmental effects such as DES concentrations, pH levels, and temperature on the strain’s degradation ability were tested. Degradation metabolites of DES by strain JF were analysed via high performance liquid chromatography (HPLC) and liquid-chromatography time of flight mass spectrometry (LC-TOF-MS). Results indicated that B. subtilis JF can effectively degrade DES within a concentration of 25–200 mg/L. Increasing pH levels (pH > 7) are reported to increase the degradation rate of DES by the strain. The optimal temperature for strain JF to degrade DES was identified as 45 °C. In this study, 4, 4’-hexene oestrogen quinones (DESQ) and DES-4-semiquinone were speculated as two degradation metabolites of DES, and both can be completely degraded by strain JF. A slight reduction of DES in the blank system (DES cultured in Luria-Bertani (LB) medium without strain JF) was observed in this study. The reduction trend in the blank system only occurred during the first few days (about 4 days), and was considerably lesser than the decomposition and transformation effect of DES via strain JF. Furthermore, the metabolite DESQ could not be further decomposed in blank LB medium without strain JF. All the results demonstrate that complete degradation of DES in the fermentation broth occurs due to the function of strain JF rather than organic decomposition. In conclusion, the high efficiency of degradation and the potential to degrade DES completely indicates that strain JF has potential for the bioremediation of DES-contaminated environments (soil, river, and so on) and fermented foods.